Antipyretic Activity of Mentaos Leaf Extract (Wrigthia pubescens R.BR.) in male white rats of the Pepton-induced strain of Wistar - Kristyanti, Yulia; More, Evanisia More; Bire, Winioliski L.O. Rohi; Wadhi, Maria Nuari Putri (LPPM Universitas Dhyana Pura, 2025)
Fever is a condition where the body temperature exceeds 37°C above the normal limit. The administration of antipyretic drugs aims to reduce the temperature in the hypothalamus by inhibiting the enzyme cyclooxygenase, which prevents the formation of prostaglandins. The mentaos plant (Wrightia pubescens R.BR.) is known to have flavonoid, tannin, saponin, alkaloid, and steroid chemical compounds. The purpose of this study was to determine the antipyretic activity of mentaos leaf extract (Wrightia pubescens R.BR.) and to determine the most optimal dose as an antipyretic from mentaos leaf extract (Wrightia pubescens R.BR.). The method used was the pretest-posttest-only control design method. Group I was given Na-CMC 0.5% as a negative control, Group II was given paracetamol 9 mg/kgBB as a positive control, and Groups III, IV, and V were given mentaos leaf extract at doses of 120 mg/kgBB, 160 mg/kgBB, and 200 mg/kgBB, respectively. The results of statistical analysis showed that there was antipyretic activity in the three doses of mentaos leaf extract (Wrightia pubescens R.BR.) and that the optimal antipyretic effect was in the third dose group of mentaos leaf extract, 200 mg/KgBB.